Psychological symptoms and patterns of mobile application use for young adult cancer survivors. Issue 7 (28th March 2021) - Ahmad, Zeba N.; Benedict, Catherine; Hotchkiss, Maiya; Ford, Jennifer S.
Key Points: What's already known about this topic? Young adult (YA; aged 18–39) cancer survivors report social isolation and unmet needs for social, emotional, and informational support. Mobile health applications offer a unique and scalable opportunity to provide access to YA peers and other resources, overcoming geographical distance and financial burden App features such as group chats, private messaging and "matching" to peers by age or cancer type serve to build relationships between YA survivors. Despite reporting moderately high perceived socioemotional support from their existing networks, YAs with more frequent symptoms of anxiety were the most likely to use the private messaging feature on the app. In addition to targeting supportive mobile health apps to YA survivors, assessing the mental health status of users and observing patterns of app usage can be used to tailor and improve uptake and utility.